Madrasah Head Policy in Improving the Quality of Teacher Profession - Hasanah, Aswatun; Nonitasari, Ipon; Habibah, Hasna (Universitas Malikussaleh, 2020)
This study examines the policies of Islamic elementary school heads in improving the quality of the profession of Islamic elementary school teacher. The focus of the discussion on this research is how the teacher's profession is, how to improve the quality of the teacher profession, how to evaluate in improving the quality of the teacher profession. This research uses a qualitative approach with field study methods. The results of this study show that the policy of the head of Islamic elementary school in improving the quality of the teacher profession in MI Ma'arif Saman Bangunharjo Sewon Bantul Yogyakarta as follows: 1) Make himself (Islamic elementary school head) as an example. 2) Include Training, Training or Workshop. 3) Activate Teachers In Professional Organizations. 4) Conduct Class Action Research (PTK). 5) Supports improving teacher qualifications. 6) Follow The Latest News. And In order to conduct supervision to improve the professional competence of teachers, there are several things that need to be done by the head including 1) Making a visit to the classroom. 2) Monitor extracurricular activities. 3) Conduct administrative examination of Teaching Learning Activities (KBM). 4) Give a direct reprimand. The supporting factor in improving the quality of the teacher profession is the first of the seriousness of the madrassa head to the main capital as well as his commitment to improving the quality of Islamic elementary school. Both enthusiasm teachers to make improvements from the problems that arise in order to improve the quality of their profession. While the inhibitory factor in improving the quality of the teacher profession is the availability of infrastructure facilities that are still minimal.